Non-covalent binding analysis of sulfamethoxazole to human serum albumin: Fluorescence spectroscopy, UVâvis, FT-IR, voltammetric and molecular modeling - Praveen N. Naik; Sharanappa T. Nandibewoor; Shivamurthi A. Chimatadar (Elsevier, 2015)
This study was designed to examine the interaction of sulfamethoxazole (SMZ) with human serum albumin(HSA). Spectroscopic analysis of the emission quenching at different temperatures revealed that the quenching mechanism of human serum albumin by SMZ was static mechanism. The binding constant values for the SMZâHSA system were obtained to be 22,500Â L/mol at 288Â K, 15,600Â L/mol at 298Â K, and 8500Â L/mol at 308Â K. The distance r between donor and acceptor was evaluated according to the theory of FÃ¶ster energy transfer. The results of spectroscopic analysis and molecular modeling techniques showed that the conformation of human serum albumin had been changed in the presence of SMZ. The thermodynamic parameters, namely enthalpy change (âH0) â36.0Â kJ/mol, entropy change (âS0) â41.3Â J/molÂ K and free energy change (âG0) â23.7Â kJ/mol, were calculated by using van×³t Hoff equation. The effect of common ions on the binding of SMZ to HSA was tested. Keywords: Human serum albumin, Sulfamethoxazole, Fluorescence quenching study, Static mechanism